NAMES OF DISHES ADAPTED FROM ENGLISH, RUSSIAN, AND UZBEK LANGUAGES - Bobojonova Zarina Rashidovna (Web of Journals Publishing, 2024)
The words of a language can be traced to two sources. Some have been a part of that same language as far back as its history is known, although, since no language remains fixed, they will have gradually changed in form and sound. Others are loanwords, borrowed from another language with which the speakers of the first have been in contact. Food words fall into both categories. Food and drink are necessities of life, basic elements of which are likely to remain fixed (and to retain the same vocabulary) through the centuries. Yet innumerable details will change (and demand new names) in response to taste, fashion, and the love of variety; also in response to the migration of peoples, the development of trade, and the transplanting of food species. Thus in English the names of foods and drinks mirror the cultural history of English speakers. Some names remain unexplained: no one knows the origin of "raspberry," "syllabub," or "toffee."
Keywords: Etymology, food, connection of English, and Uzbek foods, borrowed names of dishes in Russian.